Density functional static dipole polarizability and first-hyperpolarizability calculations of Na-n (n=2, 4, 6, 8) clusters using an approximate CPKS method and its comparison with MP2 calculations - Sophy, K. B.; Calaminici, Patrizia; Pal, Sourav (Journal of Chemical Theory and Computation, 2007)
{We report the static dipole polarizability and first-hyperpolarizability of the sodium atom clusters, Na-n

Systematic comparison of DFT and CCSD dipole moments, polarizabilities and hyperpolarizabilities - Karne, Anagha S.; Vaval, Nayana; Pal, Sourav; Vasquez-Perez, Jose M.; Koester, Andreas M.; Calaminici, Patrizia (Chemical Physics Letters, 2015)
A comparative study of dipole moments, polarizabilities and hyperpolarizabilities of 16 different molecules is performed employing two completely different theoretical approaches namely, density functional theory (DFT) and coupled cluster singles and doubles (CCSD). Both methods include electron correlation. The CCSD method is more accurate but highly expensive. DFT with auxiliary density allows non-iterative solutions which is computational advantage and useful for large molecules. Dipole moments and polarizability calculations from DFT are in very good agreement with CCSD calculations. However, negative hyperpolarizability values from DFT differ significantly from their CCSD counterparts, whereas positive hyperpolarizabilities show reasonable agreement between these methodologies. (C) 2015 Elsevier B.V. All rights reserved.

Systematic comparison of DFT and CCSD dipole moments, polarizabilities and hyperpolarizabilities (vol 635, pg 168, 2015) - Karne, Anagha S.; Vaval, Nayana; Pal, Sourav; Vasquez-Perez, Jose M.; Koester, Andreas M.; Calaminici, Patrizia (Chemical Physics Letters, 2015)